Mechanistic insights into promotion of non-small cell lung cancer by BAG5 using integrative multi-omics approaches - Huang, Jing-Shan; Wang, Jia-Mei; Yuan, Ye; Zhang, Ting; Li, Bai-Qiang; Zhao, Fu-Ying; Hao, Liang; Yu, Zhan-Wu; Wang, Hua-Qin (Frontiers in Immunology, 2025)
IntroductionWith the continuous emergence of new technologies in omics, the integrative analysis of multi-omics data has become a new direction to explore life mechanisms. The Bcl-2 associated athanogene (BAG) family consists of co-chaperones involved in various cellular processes, including stress signaling, cell cycle regulation, and tumorigenesis. BAG5, a unique member of this family, contains multiple BAG domains, yet its role in non-small cell lung cancer (NSCLC) remains largely unexplored.MethodsIn this study, we employed a multi-omics approach, integrating single-cell transcriptomics, proteomics, interactomics, and phosphoproteomics data to comprehensively investigate BAG5 function in NSCLC. Functional analyses were performed using cell lines and patient-derived organoids (PDOs) to validate our findings.ResultsOur results demonstrate that BAG5 plays a critical role in the regulation of RNA metabolism, mitochondrial dynamics, and metabolic reprogramming. Additionally, BAG5 is involved in cytoskeletal remodeling and epithelial-to-mesenchymal transition (EMT), contributing to the proliferation and invasion of NSCLC cells.DiscussionThese findings underscore the potential oncogenic role of BAG5 in NSCLC, revealing that it acts through multiple molecular pathways. Our study suggests that targeting BAG5 could be a promising therapeutic strategy for treating NSCLC.